Membership in team science institute enhances diversity of researchers’ collaboration networks - Barley, William C.; Dinh, Ly; Johnson, Lauren P.; Allan, Brian F. (PloS one, 2025)
Interdisciplinary scientific teams are subject to a complex constellation of potential benefits, such as enabling innovation, and challenges, such as increased conflict and failure. Given these tensions, scholars and practitioners are increasingly interested in the role that organizational policies and resources can play in potentially mitigating the challenges faced on interdisciplinary teams. We report results from quantitative case study of a research institute dedicated to providing resources to enable interdisciplinary scientific teams, to examine how joining an organization with resources devoted to interdisciplinarity affected researchers’ collaborations. We adopt bibliometric network techniques to explore the productivity and diversity of scientists’ collaborations before and after joining the institute. Generalized linear mixed-effect modeling shows a significant increase for researchers in their number of papers and co-authors after joining the institute. Comparison to a matched pair control group indicates researchers who joined the institute experienced a significantly greater increase in their diversity of co-authors, and no relative decrease in the number of papers produced, despite challenges inherent to interdisciplinary collaboration. These findings suggest institutional resources can operate to broaden collaboration diversity without harming researcher productivity, which has important implications for team science and science policy.